The Existence of Cheap Markets in Controlling Inflation on People's Purchasing Power - Sholatiah, Sholatiah; Desi Erawati; Tri Hidayati (Universitas Muhammadiyah Prof. DR HAMKA., 2025)
This study aims to analyze the role and existence of cheap markets in controlling inflation and its impact on people's purchasing power. Uncontrolled inflation can reduce purchasing power, especially for low-income groups, so government intervention through effective policies is needed. One policy that is often applied is the organization of cheap markets as an effort to provide basic needs at more affordable prices. This research uses a qualitative approach, focusing on case studies of cheap markets in various regions in Indonesia. The results show that cheap markets have a significant role in helping to stabilize the price of basic necessities and increase people's purchasing power, especially during periods of high inflation. This research suggests that cheap market programs should be expanded and tailored to local needs, as one of the strategies in controlling inflation and improving people's welfare